Synthesis, Characterization, Biological, and Antioxidant Activity of New Metal Ion Complexes with Schiff Base Derived from 2-Hydroxybenzohydrazide - Kadhim, Ayyat Jawad; Shaalan, Naser (Indonesian Journal of Chemistry, 2024)
The study involved the synthesis of new complexes with tetradentate ligand (LH). The general formula of complexes was [M(LH)(H2O)2] with M of Ni2+, Co2+, Cu2+, and Zn+. The ligand was synthesized by treating the 2-hydroxybenzohydrazide with salicylaldehyde. The structural characteristics of ligands and complexes were analyzed using various techniques, including elemental analyses, magnetic susceptibility, molar conductivity, infrared, ultraviolet absorption, mass, and NMR spectroscopy studies. The physical measurements indicated that the prepared complexes are non-electrolyte and showed that the ligand is tetradentate when coordinated with metal ions through the nitrogen of azomethine (–C=N–), two oxygen atoms of O–H phenolic, and an oxygen atom of carbonyl (C=O) for benzohydrazide. It was found that Co2+, Cu2+, and Zn2+ complexes are octahedral, while Ni2+ complexes are square planar. The biological screening of the complexes demonstrates that the Schiff base metal complexes exhibit remarkable efficacy in combating microorganisms by utilizing Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli) bacteria, as well as Candida albicans fungi. Hence, their results were good in inhibition. Then, the potential of these prepared compounds as antioxidants was determined by inhibiting free radicals.